Simon Stevin - Dijksterhuis, E.J. author. aut Link
152 p.
Keywords: The works of Simon Stevin are most interesting for the history of science, because they have such a wide scope and reflect so clearly the development of scientific knowledge around 1600 in central Europe. The recent publi cation of his Principal Works, with an English translation, has again attracted attention to his fascinating personality. The book on Stevin by Professor E. J. Dijksterhuis, originally published in the Dutch language, is an excellent introduction to the life and works of this remarkable Netherlander. Dijksterhuis prepared a somewhat condensed English edition, adapted to the foreign reader. Because of his untimely death, publication had to be deferred until the undersigned were able to undertake the editorial work. The Royal Netherlands Academy of Sciences, Amsterdam, allowed a grant, through which a linguistic revision of the text was made possible. We are very grateful to Miss C. Dikshoorn for the care with which she carried out this task and prepared the text for the press. A few supplementary notes have been added, for which we are personally responsible and which have been marked with our initials (R.H. or M.M.). Messrs Martinus Nijhoff, The Hague, who published the original Dutch edition, have kindly agreed to bring out also the English version and have given all their attention to this publication. R. HOOYKAAS M. G. J. MINNAERT INTRODUCTION Modern science was born in the period beginning with Copernicus's work De Revolutionibus Orbium Coelestium (l543) and ending with Newton's Philosophiae Naturalis Principia Mathematica (1687).